QSroute: Enhancing Software Defined Networking Routing Scheme through Advanced QoS Metrics Integration - Kamarudin, Imran Edzereiq; Ameedeen, Mohamed Ariff (JOIV : International Journal on Informatics Visualization, 2025)
The surge in global internet traffic, primarily fueled by the rise of streaming platforms, cloud computing, and data-intensive applications, has posed significant challenges in effectively managing network resources. Ensuring consistent Quality of Service (QoS) across various types of traffic, such as video streaming, online gaming, and real-time communications, is becoming an increasingly challenging task. Traditional routing techniques, such as best-effort and shortest-path methods, are increasingly falling short in meeting these demands due to their inability to account for different traffic requirements. To address these limitations, this paper introduces QSroute, a novel QoS-based routing (QBR) scheme specifically designed for Software Defined Networking (SDN) environments. QSroute leverages the global view provided by SDN to dynamically optimize routing decisions based on critical QoS metrics, including available bandwidth, packet delay, and packet loss ratio. Our approach computes the optimal path between source and destination nodes by minimizing a composite link cost derived from these metrics. Extensive simulation results show that QSroute significantly outperforms existing QBR schemes, particularly in terms of reducing end-to-end delays, minimizing jitter, and improving overall throughput. These performance gains underscore QSroute’s potential as a highly effective solution for addressing the complex demands of modern network environments, offering enhanced scalability and network efficiency. Future research will investigate the integration of additional QoS metrics, as well as the scheme's scalability in more complex, multi-domain SDN environments, to further enhance its applicability.